Is murine gammaherpesvirus-68 (MHV-68) a suitable immunotoxicological model for examining immunomodulatory drug-associated viral recrudescence?. (January 2015) - Aligo, Jason; Walker, Mindi; Bugelski, Peter; Weinstock, Daniel
Abstract Immunosuppressive agents are used for treatment of a variety of autoimmune diseases including rheumatoid arthritis (RA), systemic lupus erythematosis (SLE), and psoriasis, as well as for prevention of tissue rejection after organ transplantation. Recrudescence of herpesvirus infections, and increased risk of carcinogenesis from herpesvirus-associated tumors are related with immunosuppressive therapy in humans. Post-transplant lymphoproliferative disorder (PTLD), a condition characterized by development of Epstein Barr Virus (EBV)-associated B-lymphocyte lymphoma, and Kaposi's Sarcoma (KS), a dermal tumor associated with Kaposi Sarcoma-associated virus (KSHV), may develop in solid organ transplant patients. KS also occurs in immunosuppressed Acquired Immunodeficiency (AIDS) patients. Kaposi Sarcoma-associated virus (KSHV) is a herpes virus genetically related to EBV. Murine gammaherpes-virus-68 (MHV-68) is proposed as a mouse model of gammaherpesvirus infection and recrudescence and may potentially have relevance for herpesvirus-associated neoplasia. The pathogenesis of MHV-68 infection in mice mimics EBV/KSHV infection in humans with acute lytic viral replication followed by dissemination and establishment of persistent latency. MHV-68-infected mice may develop lymphoproliferative disease that is accelerated by disruption of the immune system. This manuscript first presents an overview of gammaherpesvirus pathogenesis and immunology as well as factors involved in viral recrudescence. A description of different types of immunodeficiency then follows, with particular focus on viral association with lymphomagenesis after immunosuppression. Finally, this review discusses different gammaherpesvirus animal models and describes a proposed MHV-68 model to further examine the interplay of immunomodulatory agents and gammaherpesvirus-associated neoplasia.